Cannabis and cognitive functioning in multiple sclerosis: The role of gender. Issue 2 (June 2017) - Patel, Viral P; Feinstein, Anthony
Background: Cognitive function in people with multiple sclerosis (PwMS) is associated with gender differences and the use of smoked/ingested cannabis. Objective: The objective of this report is to explore a possible gender-cannabis interaction associated with cognitive dysfunction in PwMS. Methods: A retrospective analysis was undertaken of cognitive data collected from 140 PwMS. A general linear model was conducted to determine gender and cannabis effects on processing speed (SDMT), verbal (CVLT-II) and visual (BVMT-R) memory, and executive functions (D-KEFS), while controlling for age and years of education. Results: Cannabis was smoked at least once a month by 33 (23.6%) participants. Cannabis users were more impaired on the SDMT ( p  = 0.044). Men, who comprised 30.7% of the entire sample and 42.2% of cannabis users, were more impaired on the CVLT-II (total learning, p  = 0.001; delayed recall, p  = 0.004). A cannabis-gender interaction was found with the CVLT-II delayed recall ( p  = 0.049) and BVMT-R total learning ( p  = 0.014), where male cannabis users performed more poorly than female. Conclusion: Males with MS may be particularly vulnerable to the cognitive side effects of smoked cannabis use.